2015
DOI: 10.1097/qai.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Examining Clinic-Based and Public Health Approaches to Ascertainment of HIV Care Status

Abstract: Introduction Clinic-based tracing efforts and public health surveillance data can provide different information about HIV care status for the same patients. The relative yield and how best to use these sources to identify and re-engage out of care patients is unknown. Methods At a large public HIV clinic in San Francisco, we selected a 10% random sample of active patients who were at least 210 days “late” for an HIV primary care visit as of April 1, 2013, for clinic-based outreach. Patients were considered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Integration of surveillance data with clinical records reduced the number of patients who appeared to be out of care by half, which is similar to estimates from other settings. [18][19][20][21] Data integration also improved retention-in-care metrics and averted a substantial number of unnecessary case investigations by updating a patient's status before an investigation was initiated. Prevention of unnecessary case investigations would reduce waste and allow limited resources for patient re-engagement to be better targeted to those who truly need them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of surveillance data with clinical records reduced the number of patients who appeared to be out of care by half, which is similar to estimates from other settings. [18][19][20][21] Data integration also improved retention-in-care metrics and averted a substantial number of unnecessary case investigations by updating a patient's status before an investigation was initiated. Prevention of unnecessary case investigations would reduce waste and allow limited resources for patient re-engagement to be better targeted to those who truly need them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in specific clinics in Los Angeles, San Francisco, Seattle, and Chicago found that 45-52% of patients classified as ''out of care'' according to clinic medical records, in fact, had records of death, relocation, or evidence of care at another facility in state HIV surveillance databases. [18][19][20][21] These findings highlight the importance of collaboration between healthcare providers and state health departments in patient re-engagement efforts. However, it is unclear whether these estimates hold for other geographic settings and to what extent ongoing integration of HIV surveillance data in a clinic's re-engagement activities would impact the amount of resources needed to manage case loads.…”
Section: Introductionmentioning
confidence: 99%
“…131 Coordination with public health surveillance data systems is important, when possible, to improve linkage to, retention in, and reengagement in care. 7,132 …”
Section: Engagement In Care and Art Adherencementioning
confidence: 99%
“…Thus, clinic-based tracking and surveillance registry matching substantially reduced an estimate of the cumulative incidence of those lost to care over three years based on patient visit information alone. 44 …”
Section: Synthesis Of Echpp-2 Continuum Of Care Manuscriptsmentioning
confidence: 99%